Peran Digitalisasi Dalam Meningkatkan Kinerja Administrasi Publik : Sebuah Kajian Literatur - Anisatur Rahma Adawiyah; Viona Zanesta; Arizka Putri Barus; Boni Saputra; M. Fachri Adnan (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
Digital transformation has become a central agenda of bureaucratic reform in Indonesia. This study aims to analyze the role of digitalization in improving public administration performance through a literature review approach covering twenty academic articles published between 2020 and 2025. Using a thematic analysis framework based on Good Governance dimensions, the study finds that digitalization consistently contributes to improvements in efficiency, transparency, accountability, and responsiveness of public administration. However, the effectiveness of this contribution is conditional and moderated by digital human resource capacity, technology infrastructure quality, leadership commitment, and regulatory conduciveness. The study also identifies three major research gaps: the scarcity of multidimensional studies, the lack of inter-regional comparative research, and the absence of integrative frameworks. This article contributes to the development of a conceptual model of the digitalization-public administration performance relationship.